2020
DOI: 10.1108/jarhe-10-2019-0272
|View full text |Cite
|
Sign up to set email alerts
|

A survey of study skills of first-year university students: the relationships of strategy to gender, ethnicity and course type

Abstract: PurposeNot all students who did well in high school are successful in college, particularly in science, technology, engineering and math (STEM) majors with the most affected student groups including women, first-generation or historically disadvantaged students. Certain study skills may be associated with greater success in college, yet these skills may be less regularly used by those underrepresented groups.Design/methodology/approachThis paper reports the results of a survey given to several hundred newly-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
2
9
3
Order By: Relevance
“…We did not find a significant effect of gender, race, or age on the study strategy choice of our students. This is unlike the results found in Williams et al (2021), which found students historically excluded based on race are less likely to start college using self-testing, and women are more likely to start college using underlining, highlighting, and flash cards. The lack of significant effect of demographics in our study may be because of the small sample size (and thus lack of power in our test).…”
Section: Research Question 1: What Study Skills Do Students Use?contrasting
confidence: 99%
See 4 more Smart Citations
“…We did not find a significant effect of gender, race, or age on the study strategy choice of our students. This is unlike the results found in Williams et al (2021), which found students historically excluded based on race are less likely to start college using self-testing, and women are more likely to start college using underlining, highlighting, and flash cards. The lack of significant effect of demographics in our study may be because of the small sample size (and thus lack of power in our test).…”
Section: Research Question 1: What Study Skills Do Students Use?contrasting
confidence: 99%
“…Community college students also used spacing at the end of the course at levels higher than many undergraduates. They did not, however, increase their self-testing (50%) to levels equivalent to other undergraduate surveys, found to be 71% in Hartwig and Dunlosky (2012), 72% in Morehead et al (2016), and 62% in Williams et al (2021).…”
Section: Research Question 1: What Study Skills Do Students Use?contrasting
confidence: 51%
See 3 more Smart Citations